The negative role of environmental pollution on international trade: Strategy recommendation to solve this problem - Yüksel, Serhat; Ubay, Gözde Gülseven; Çelebi, Büşra (IGI Global, 2021)
The purpose of this study is to determine the main causes behind companies causing carbon emissions. In this way, the main reasons for companies to make carbon emissions have been explored. For this purpose, six different variables that are thought to be effective on this issue were determined. After that, an examination was made with fuzzy DEMATEL method in order to determine which of these factors are more important. The findings indicate that legal deficiency is the main reason for companies to cause carbon emissions. In this situation, it is a must to take necessary measures for the solution of this problem. In order for overcome legal deficiency problem, it is understood that the legal infrastructure should be adapted to this process. In order to increase the international trade volume, it is necessary to impose penal sanctions on companies and to regularly inspect these companies. In addition to these, incentives can be given to companies that are in competitive sectors and to create an awareness on this subject, governments can facilitate training programs.
Keywords: Strategy Recommendation; International Trade; Environmental Pollution